2013
DOI: 10.1177/0004867413492219
|View full text |Cite
|
Sign up to set email alerts
|

Systematic meta-analysis of individual selective serotonin reuptake inhibitor medications and congenital malformations

Abstract: Fluoxetine and paroxetine should be avoided in the first trimester and among those at risk of an unplanned pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
94
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 55 publications
13
94
3
2
Order By: Relevance
“…A meta-analysis of first trimester exposure to several classes of antidepressant confirmed these observations . Additionally, a meta-analysis found an increased risk of major malformations with fluoxetine and paroxetine exposure specifically in the first trimester (Myles et al, 2013). Although studies continue to examine this endpoint, the data do not point to a significant Prenatal Antidepressant Exposure association of prenatal antidepressant exposure and a specific pattern of congenital malformations.…”
Section: E Associations With Congenital Malformationsmentioning
confidence: 99%
“…A meta-analysis of first trimester exposure to several classes of antidepressant confirmed these observations . Additionally, a meta-analysis found an increased risk of major malformations with fluoxetine and paroxetine exposure specifically in the first trimester (Myles et al, 2013). Although studies continue to examine this endpoint, the data do not point to a significant Prenatal Antidepressant Exposure association of prenatal antidepressant exposure and a specific pattern of congenital malformations.…”
Section: E Associations With Congenital Malformationsmentioning
confidence: 99%
“…Thereafter, starting with paroxetine [22], the SSRIs have come under scrutiny particularly in relation to congenital heart defects (CHD) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Although not all studies have supported this association [38][39][40][41][42][43][44][45], meta-analyses have found positive overall evidence [46][47][48][49][50]. Some non-CHD congenital anomalies have also been linked to SSRI exposure in first trimester pregnancy [24,29,32,[34][35] although this literature is much smaller.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31] However, paroxetine and most recently fluoxetine are two SSRIs for which increasing evidence shows negative effects on the fetus. A recent meta-analysis by Myles et al 27 indicated that paroxetine (odds ratio [OR] = 1.29, 95% confidence interval [95%CI] 1.11-1.49) and fluoxetine but not sertraline or citalopram were associated with a higher risk of major malformations. Conversely, Grigoriadis et al 28 have reported that paroxetine and fluoxetine were not significantly related to major congenital malformations.…”
Section: Congenital Malformationsmentioning
confidence: 99%
“…32 Three meta-analyses in the literature have reported odds ratios between 1.12 (95%CI 0.98-1.28) and 1.25 (95%CI 1.03-1.51) for congenital defects associated with fetal exposure to fluoxetine. 27,28,32 Although there are conflicting reports published, a greater number of studies on the use of paroxetine describe deleterious effects such as increased risk of cardiac malformations. 24,[26][27][28]31,[33][34][35] This increased risk is also supported by two recent meta-analyses (reported OR = 1.43, 95%CI 1.08-1.88 and 1.44, 95%CI 1.12-1.86).…”
Section: Congenital Malformationsmentioning
confidence: 99%
See 1 more Smart Citation